EVALUASI PENCATATAN DAN PELAPORAN REKAM MEDIS PADA PENYAKIT TUBERKULOSIS DI RSIA ILANUR TANGERANG - Eki Maulana; Muniroh (Yayasan Nusantara Hasana Berdikari, 2023)
Recording is an activity or process of documenting an activity in written form. Reports are records that provide information about certain activities and the results are submitted to the authorized party or related to these activities. Tuberculosis (TB) is a leading cause of poor health, one of the top 10 causes of death worldwide. RSIA Ilanur is a private hospital that serves mothers and children which was established in 2016. The purpose of the study was to identify the implementation of recording and reporting of medical records on Tuberculosis at RSIA Ilanur Tangerang, this study aims to get an overview of the recording and reporting of Medical Records on diseases Tuberculosis at RSIA Ilanur Tangerang. The method used in this descriptive study is to describe and describe the quality of recording and reporting on Tuberculosis. The collection technique used the instruments of observation, interviews, checklists, and reference books. The results of the study there are SOPs for Recording and Reporting TB Case Patients. And it has been socialized until now, but not all officers carry out its implementation according to the procedures in carrying out recording and reporting on TB patients (which are not according to procedures 35.38%). The constraint factor in recording and reporting TB cases is the lack of human resources in the relevant sections, manual recording in outpatients does not run optimally because TB patients have not been centered on the DOTS TB poly. Suggestions that hospitals should provide human resources, computerized systems and facilities should be more available as needed because it can facilitate officers in carrying out their implementation, which currently are all integrated systems from SIMRS to systems from the government.